From Slaves to Supporters: The Role of the Slavs in the Fatimid Mediterranean Empire in the Fourth/Tenth Century - Jiwa, Shainool (Mediaeval studies, 2015)
The article explores the role played by slaves in North Africa's Fatimid state in 297/910. Topics discussed include the prominence of the Saqaliba slaves in major areas of Fatimid administration and in its households, challenges faced by the state in its rule of North Africa and accounts discovered from sources written by Fatimid Ismaili authors from the 14th/10th century that includes reasons behind the Saqalibas' great influence in the state.